Aphrodisiac properties of Aquilaria malaccensis leaves aqueous extract in ICR mice - Husni Ibrahim (Tanjong Malim, 2019)
Aphrodisiac properties of Aquilaria malaccensis leaves aqueous extract in ICR mice by Husni Ibrahim